2017
DOI: 10.21037/jtd.2017.04.03
|View full text |Cite
|
Sign up to set email alerts
|

Whack-a-mole strategy for multifocal ground glass opacities of the lung

Abstract: Ground glass opacity (GGO) is a good prognostic indicator for lung cancer and is useful for physicians to predict prognosis. Due to recent advances in computed tomography (CT), the chance to encounter GGO is rapidly increasing in clinical practice. Based on the studies on radiological pathological correlation, GGO represents pathological lepidic growth and consolidation on CT represents pathologically invasive components. Thus, consolidation tumor ratio 0.5 or less means pathological less invasiveness for lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 50 publications
0
27
0
Order By: Relevance
“…The treatment strategies and prognosis are not different in terms of the nodule number or size. [11][12][13] Kim et al 14 reported that 73 patients underwent pulmonary resection for bronchioloalveolar carcinoma, of whom 23 had multiple GGOs seen on preoperative CT. In the 18 patients who did not have all GGO lesions resected, none of the residual GGO lesions progressed in size or solidity during followup for a median of 40.3 months.…”
Section: Follow-upmentioning
confidence: 99%
“…The treatment strategies and prognosis are not different in terms of the nodule number or size. [11][12][13] Kim et al 14 reported that 73 patients underwent pulmonary resection for bronchioloalveolar carcinoma, of whom 23 had multiple GGOs seen on preoperative CT. In the 18 patients who did not have all GGO lesions resected, none of the residual GGO lesions progressed in size or solidity during followup for a median of 40.3 months.…”
Section: Follow-upmentioning
confidence: 99%
“…The presence of ground glass opacity (GGO) in a chest computed tomography scan (CT Scan) is a radiological entity that has been booming, mostly after the initiation of screening tests for lung cancer (1)(2)(3). Particularly the GGO lesions have been related with non-small cell lung cancers (NSCLCs) specifically the lepidic component of adenocarcinomas (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly the GGO lesions have been related with non-small cell lung cancers (NSCLCs) specifically the lepidic component of adenocarcinomas (1,2). It is necessary to classify this according to its radiological characteristics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The management of GGO-associated adenocarcinoma is more nuanced. 3 There is little controversy that surgical resection is indicated for part-solid GGO, because the solid component is invasive cancer nested within the noninvasive lepidic adenocarcinoma (lepidic-positive adenocarcinoma). The magnitude of lung resection is influenced by tumor characteristics (sizes and the proportions of solid component within the GGO, consolidation tumor ratio) as well as patients' underlying conditions.…”
mentioning
confidence: 99%